(3OhQ GdEOGQI aj GdJfHD HGdaTd GdeGdj ddTQcGJ HEWGQ EfehPL BdJeGf (B/s - (3GdLLGhj, WdGd eMeO Ydjs; (3GdRHjOj, HdGSe eMeO GHQGgje s ((3YeGf(B: s (3OGQ GdGjGe ddfTQ hGdJhRjY(B, s, 2015)
(3SJhjGJ GdGOGQI hhXGFagG h GdJNWjW h GgejI GdGOGQI h eJZjQGJgG h caGAI GdGOGQI GdYdjG h aGYdjI fXGe GdQbGHI GdOGNdjI h GSJbdGdjI eQGbH GdMSGHGJ ceG Je GdJWQb Gdi GdJfHD HGdaTd GdeGdj HJfGhd ESJNOGe GdJMdjd GdeGdj cGOGI ddJfHD HGdaTd GdeGdj h CSHGH GdaTd GdeGdj h GdJfHD Hg h edGAeI aQV GdGSJeQGQjI h GdbjeI GdShbjI dMb GdedcjI Gdi eLehY GdeWdhHGJ h GdeHjYGJ Gdi eLehY GdehLhOGJ ceG Je JfGhd GdJMdjd GdeGdj hhUa h JTNjU GdeJZjQGJ h CNjQG ENJHGQ aQVjGJ GdGQJHGW Hjf GdeJZjQGJ h GNJHGQ aQVjGJ GdJCKjQ Hjf GdeJZjQGJ (B.s
(3edGMb U(B.137 (3eQGLY U(B.157s
Keywords: (3GJNGP GdbQGQs; (3GOGQI GdGYeGd(B-(3NSGFQs; (3GdGOGQI GdeGdjIs